Computer video - York, Matt; Videomaker Inc. (Los Angeles : First Light Video Publishing)
This video covers the tools and techniques to get you on the road to produce professional quality videos. In six segments experts from Videomaker magazine and professional production houses share their expertise with the audience.
Host: Matt York
Keywords: Video recording; Digital video